Utilizing Multi-Theory Model in Determining Intentions to Smoking Cessation Among Smokers. (April 2019) - Nahar, Vinayak K; Wilkerson, Amanda H; Patel, Falguni C; Kim, Richard W; Stephens, Philip M; Sharma, Manoj
Background: Smoking is a risk factor for lung cancers, and a myriad of other acute and chronic ailments. The purpose of this study was to predict initiation and sustenance of smoking cessation among smokers using a fourth-generation behavioral framework, multi-theory model (MTM) of health behavior change. Methods: A convenience sample of smokers from a shopping mall in rural, Appalachian Kentucky county was invited to participate in this cross-sectional study. A 38-item, face and content validated, MTM-based survey instrument was administered to the participants. Results: A total of 148 participants completed the study. The mean age of the participants was 35.53 (SD = 14.52) years. Most were male (58.1%) and Caucasian (95.9%). Participants reported smoking for an average of 16.45 (SD = 13.12) years. Participatory dialogue (β = 0.235, P = .003) and behavioral confidence (β = 0.305, P = .005) were significant predictors of intention for initiation for smoking cessation behavior. Emotional transformation (β = 0.319, P = .001) was a significant predictor of intention for sustenance for smoking cessation behavior. Discussion: Two of the MTM constructs for initiation and one of the MTM constructs for sustenance of change accounted for a moderate amount of variance in initiation and sustenance of smoking cessation behavior among community members in a rural, Kentucky county. MTM has utility for predicting both initiation and sustenance of smoking cessation behavior. Future interventions using MTM constructs should be developed for smoking cessation behavior change.